The effect of the maximum physical effort on some physiological variables, body components and achievement level in the effectiveness of air rifle shooting - AbdulHameed, Ghusoon Natiq; Salman, Thaer Dawood (International Journal of Psychosocial Rehabilitation, 2020)
The job that confronts players with the effectiveness of shooting with an air rifle is high, so it requires necessary functional adaptations that differ in their degrees from other sports. Regular training in air rifle shooting leads to physiological changes in most of the body's internal systems, and changes and responses can be identified. The functional accompanying physical activity through the presence of body components that reflect these physiological changes in the form of changes in some components, and the importance of research lies in studying the physiological changes accompanying the maximum physical effort and the consequent development of the level of achievement in the effectiveness of shooting with air rifle and body components during rest and after performance Maximum physical effort, and the research objectives were as follows: 1. Identify the changes that occur in the level of some physiological variables before and after performing the maximum physical exertion. 2. Identify the changes that occur in the components of the body before and after performing the maximum physical exertion. 3. Identify the changes that occur in the level of achievement in the effectiveness of shooting with an air rifle before and after performing the maximum physical effort. As for the research hypotheses, they are: 1. There are significant differences in the level of some physiological variables before and after the performance of the maximum physical exertion and in favor of post-measurement.2. The presence of significant differences in the components of the body before and after the performance of the maximum physical exertion and in favor of dimensional measurement. 3. There are significant differences in the level of achievement in the effectiveness of shooting with an air rifle before and after performing the maximum physical effort and in favor of telemetry. The researchers used the descriptive method, and the research sample consisted of (10) female players emerging with air rifle shooting, and (8) physiological tests and (5) body components and a level of achievement in the air rifle were used.